2004
DOI: 10.1002/ejoc.200300684
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the B Ring in Steroids and Hopanoids from Squalene

Abstract: A theoretical conformational study based on density functional calculations provides evidence that the sterol and nonsterol cyclizations of squalene to triterpenes are controlled by conformational effects as has been previously suggested. It was found that different conformers of a model system of squalene give rise to the chair−boat conformation found in the steroids and the chair−chair conformation of the pentacyclic 3‐deoxytriterpenes for their A and B rings. It is suggested that the enzymes play a key role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The stabilizing effect of the 20-oxa substitution comes into play only as the annulation process nears completion and thus does not influence the activation energy. The transition states and activation energies closely resemble computational results for protosteryl cation formation by Hess,7d who first proposed bridged transition states in C-ring expansion/D-ring formation as an alternative to anti-Markovnikov intermediates. ,7b,j,p
2 Changes in energy (A) and geometry (B) from path calculations modeling 17β-dammarenyl cation formation with and without the 20-oxygen. Energies in panel A are from mPW1PW91/6-311+G(2d,p)//B3LYP/6-31G* calculations.
…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The stabilizing effect of the 20-oxa substitution comes into play only as the annulation process nears completion and thus does not influence the activation energy. The transition states and activation energies closely resemble computational results for protosteryl cation formation by Hess,7d who first proposed bridged transition states in C-ring expansion/D-ring formation as an alternative to anti-Markovnikov intermediates. ,7b,j,p
2 Changes in energy (A) and geometry (B) from path calculations modeling 17β-dammarenyl cation formation with and without the 20-oxygen. Energies in panel A are from mPW1PW91/6-311+G(2d,p)//B3LYP/6-31G* calculations.
…”
Section: Resultssupporting
confidence: 69%
“…We optimized likely transition-state structures leading to the hopyl and lupyl cations ( 5 and 15 ). Their geometries, shown in Figure , indicate that the transition state for D-ring expansion/E-ring formation, like that of C-ring expansion/D-ring formation,7d occurs during ring expansion and before closure of the new ring. These transition-state structures are cyclopropane/carbonium ions and represent lower energy pathways than the 6−6−6 and 6−6−6−6 secondary carbocations that have often been invoked as intermediates in (oxido)squalene cyclization 29a…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no computational study on the overall mechanism of OSC has been reported, except that the first step (conversion R → 1 ) was studied by QM calculations on small models . The mechanism of squalene-hopene cyclase (SHC), a closely related enzyme, has been investigated in a number of computational studies, where the ring formation steps have been discussed in great detail. In the current work, we are interested in the product specificity at the hydride/methyl-shifting stage, which was never previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…For this cyclization to be concerted (6‐6‐5, chair–boat formation), a conformation of the squalene oxide must exist that once protonated has the electrophilic CC double bonds positioned to interact with the developing positively charged carbon atoms. Our earlier studies on the individual cyclizations have shown that for a concerted cyclizations to occur, the conformation about the key CC bond must not exist as a minimum if a positive charge is developed in the vicinity of the achimerically assisting double bond that supplies the electrons for the newly forming CC σ bond 9c,d…”
Section: Methodsmentioning
confidence: 99%